IMPLEMENTASI ALAT PERMAINAN EDUKATIF BATTIK PADA PEMAHAMAN MATA PELAJARAN IPAS KURIKULUM MERDEKA SISWA KELAS IV MADRASAH IBTIDAIYAH - Amalia, Nur Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of APE BATTIK (Alat Permainan Edukatif Budaya, Akhlak, Kritis, Kreatif, Inovatif, Ketuhanan) in the IPAS subject with the topic "My Indonesia is Rich in Culture" in 4th grade at MI Nurul Islam. The research method used is descriptive qualitative with data collection tools of observation, interviews, documentation and tests. Data analysis techniques use data and method triangulation. The results of the study indicate that the implementation of APE BATTIK in the Science subject with the material My Indonesia is Rich in Culture in class IV significantly increases students' active involvement in learning and improves student learning outcomes. In learning activities, students actively discuss, ask questions, and enthusiastically complete missions in matching cultural cards and questions designed like a monopoly game. Abstract science learning is made into a concrete image visualization in the form of a game. Student learning outcomes after implementing APE BATTIK reach the criteria for achieving learning objectives of 78.57%. Based on the results of this study, APE BATTIK is an alternative innovative solution to be able to improve active, interesting, fun learning activities and is able to optimize abstract understanding to be easier.